# HOW TO FIND INVERSE OF A FUNCTION

The following steps would be useful to find inverse of a function f(x), that is f-1(x).

Step 1 :

Replace f(x) by y.

Step 2 :

Interchange the variables x and y.

Step 3 :

Solve for y.

Step 4 :

Replace y by f-1(x).

Example 1 :

Find the inverse of the function f(x) = x - 5.

Solution :

f(x) = x - 5

Replace f(x) by y.

y = x - 5

Interchange x and y.

x = y - 5

Solve for y.

y = x + 5

Replace y by f-1(x).

f-1(x) = x + 5

Example 2 :

Find the inverse of the function f(x) = 3x + 5.

Solution :

f(x) = 3x + 5

Replace f(x) by y.

y = 3x + 5

Interchange x and y.

x = 3y + 5

Solve for y.

x - 5 = 3y

y = (x - 5)/3

Replace y by f-1(x).

f-1(x) = (x - 5)/3

f-1 (x)  =  (x - 5)/3

Example 3 :

Find the inverse of the function f(x) = x2.

Solution :

Replace f(x) by y.

y = x2

Interchange x and y.

x = y2

y2 = x

Solve for y.

Take square root on both sides.

y = ±√x

Replace y by f-1(x).

f-1(x) = ±√x

Example 4 :

Find the inverse of the function f(x) = log5(x).

Solution :

f(x) = log5(x)

Replace f(x) by y.

y = log5(x)

Interchange x and y.

x = log5(y)

Solve for y.

y = 5x

Replace y by f-1(x).

f-1(x) = 5x

Example 5 :

Find the inverse of the function f(x) = √(x + 1).

Solution :

f(x) = √(x + 1)

Replace f(x) by y.

y = √(x + 1)

Interchange x and y.

x = √(y + 1)

Solve for y.

x2 = y + 1

y = x2 - 1

Replace y by f-1(x).

f-1(x) = x2 - 1

Example 6 :

Find the inverse of the function f(x) = (x + 2)/(x - 5).

Solution :

f(x) = (x + 2)/(x - 5)

Replace f(x) by y.

y = (x + 2)/(x - 5)

Interchange x and y.

x = (y + 2)/(y - 5)

Solve for y.

x(y - 5) = y + 2

xy - 5x = y + 2

xy - y = 5x + 2

y(x - 1) = 5x + 2

y = (5x + 2)/(x - 1)

Replace y by f-1(x).

f-1(x) = (5x + 2)/(x - 1)

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

## Recent Articles 1. ### Definition of nth Root

Sep 29, 22 04:11 AM

Definition of nth Root - Concept - Examples

2. ### Worksheet on nth Roots

Sep 29, 22 04:08 AM

Worksheet on nth Roots